Steroidogenic Factor 1 Differentially Regulates Fetal and Adult Leydig Cell Development in Male Mice. Issue 4 (1st October 2015) - Karpova, Tatiana; Ravichandiran, Kumarasamy; Insisienmay, Lovella; Rice, Daren; Agbor, Valentine; Heckert, Leslie L.
Abstract: The nuclear receptor steroidogenic factor 1 (SF-1, AD4BP, NR5A1) is a key regulator of the endocrine axes and is essential for adrenal and gonad development. Partial rescue of Nr5a1 −/− mice with an SF-1-expressing transgene caused a hypomorphic phenotype that revealed its roles in Leydig cell development. In contrast to controls, all male rescue mice ( Nr5a1 −/− ;tg +/0 ) showed varying signs of androgen deficiency, including spermatogenic arrest, cryptorchidism, and poor virilization. Expression of various Leydig cell markers measured by immunohistochemistry, Western blot analysis, and RT-PCR indicated fetal and adult Leydig cell development were differentially impaired. Whereas fetal Leydig cell development was delayed in Nr5a1 −/− ;tg +/0 embryos, it recovered to control levels by birth. In contrast, Sult1e1, Vcam1, and Hsd3b6 transcript levels in adult rescue testes indicated complete blockage in adult Leydig cell development. In addition, between Postnatal Days 8 and 12, peritubular cells expressing PTCH1, SF-1, and CYP11A1 were observed in control testes but not in rescue testes, indicating SF-1 is needed for either survival or differentiation of adult Leydig cell progenitors. Cultured prepubertal rat peritubular cells also expressed SF-1 and PTCH1, but Cyp11a1 was expressed only after treatment with cAMP and retinoic acid. Together, data show SF-1 is needed for proper development of fetal and adult Leydig cells but with distinct primary functions; in fetal Leydig cells, it regulates differentiation, whereas in adult Leydig cells it regulates progenitor cell formation and/or survival.